CD157 and Brain Immune System in (Patho)physiological Conditions: Focus on Brain Plasticity - Lopatina, Olga L.; Komleva, Yulia K.; Malinovskaya, Natalia A.; Panina, Yulia A.; Morgun, Andrey V.; Salmina, Alla B. (Frontiers in Immunology, 2020)
Ectoenzyme and receptor BST-1/CD157 has been considered as a key molecule involved in the regulation of functional activity of cells in various tissues and organs. It is commonly accepted that CD157 catalyzes NAD+ hydrolysis and acts as a component of integrin adhesion receptor complex. Such properties are important for the regulatory role of CD157 in neuronal and glial cells: in addition to recently discovered role in the regulation of emotions, motor functions and social behavior, CD157 might serve as an important component of innate immune reactions in the central nervous system. Activation of innate immune system in the brain occurs in response to infectious agents as well as in brain injury and neurodegeneration. As an example, in microglial cells, association of CD157 with CD11b/CD18 complex drives reactive gliosis and neuroinflammation evident in brain ischemia, chronic neurodegeneration, and aging. There are various non-substrate ligands of CD157 belonging to the family of extracellular matrix proteins (fibronectin, collagen I, finbrinogen, and laminin) whose activity is required for controlling cell adhesion and migration. Therefore, CD157 could control structural and functional integrity of the blood-brain barrier and barriergenesis. On the other hand, contribution of CD157 to the regulation of brain development is rather possible since in the embryonic brain, CD157 expression is very high, whereas in the adult brain, CD157 is expressed on neural stem cells and, presumably, is involved in the neurogenesis. Besides, CD157 could mediate astrocytes’ action on neural stem and progenitor cells within neurogenic niches. In this review we will summarize how CD157 may affect brain plasticity acting as a molecule at the crossroad of neurogenesis, cerebral angiogenesis, and immune regulation.